A Control System of Cell Electroporation induced by Double Nanosecond Pulsed Electric Field. Issue 1 (February 2021) - Peng, Hao; Zhang, Lin; Liu, Xin; Guo, Fei
Abstract: A feedback linearization control system, which is used to study and analyze cell electroporation induced by double nanosecond pulsed electric field, is proposed in this paper. Then the effects of the control system which controls the process of electroporation induced by unipolar or bipolar double pulse are investigated to achieve controllability of electroporation. The simulation results show that the output of the control system, namely, the transmembrane potential can reach a stable value of 0.78 (-0.78)V, the radius increases linearly from 0.86nm to 0.88nm and the pore density increases linearly to 2.072×10 8 m −2 (2.077×10 8 m −2 ) when the input of the control system, the expected transmembrane potential is set to 0.79 (-0.79) V, and these results are in well agreement with the simulation result obtained by computing the related equations of electroporation, demonstrating that the control system developed in study can well regulate cell electroporation under the action of double nanosecond pulsed electric field. Overall, the control system can help the researcher to obtain the corresponding output electroporation parameters by directly inputting the expected transmembrane potential.